Some kinetic studies on immobilized uricase - Salleh, Abu Bakar; Ledingham, W. M. (Elsevier, 1981)
1. Uricase was immobilized onto glutaraldehyde-activated nylon tube. 2. The activity of the immobilized uricase tube was assayed by a plug-flow method adopting the integrated form of Michaelis-Menten equation. 3. Up to about 60% activity of the soluble enzyme is retained when the enzyme is derivatized. 4. Effects of changing certain parameters in the assay system were also shown. 5. The immobilized uricase has an optium pH of about 9.0, and is quite stable at 37°C when stored in borate buffer pH 9.0 in the presence of NaCl and Triton × 100.